CryoEM structure of Saccharomyces cerevisiae U1 snRNP offers insight into alternative splicing - Xueni Li (Nature Portfolio, 2017)
U1 snRNP is critical for 5′ splicing site recognition in pre-mRNA splicing. Here the authors describe the cryo-EM structure of the yeast U1 snRNP and suggest that PrpF39 is an alternative splicing factor essential for the successful recruitment of U1 snRNP by other alternative splicing factors.